Tendencias de la migración interna de la población indígena en México, 1990-2015 - Granados Alcantar, José Aurelio; Quezada Ramírez, María Félix (El Colegio de México A.C., 2018)
This article analyzes the migration of the indigenous population within internal migration processes. The aim is to characterize the sociodemographic profile of these migrants, identify the predominant migratory patterns and determine the changes that the country’s states have undergone as places of attraction and expulsion. The sources of information used are the microdata from the Population and Housing Censuses, 1990, 2000, 2010 and the Intercensal Survey 2015. We found that, for the case of the indigenous population, the predominant migratory pattern remains rural-urban and that the demographic profile of migrants is mostly males of reproductive age. Likewise, the states of Quintana Roo, Nuevo León, Sinaloa, Baja California and the State of Mexico have been consolidated as the states with the greatest attraction for indigenous migrants during the second decade of the millennium.